Implementation And Implication Of The Arabic Curriculum at MAN 1 Metro Lampung - Kuliyatun Kuliyatun; prabowo Adi Widayat; Husni Rahim; Ahmad Thib Raya (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This study aims to elucidate the implementation and implications of the Arabic language curriculum for students at Madrasah Aliyah Negeri 1 in Metro Lampung City. The study examines the application of the curriculum and the outcomes it yields for students. The study utilized a descriptive qualitative approach for research and collected data through interviews and analyzing MAN 1 Arabic curriculum documents in Metro City. The implementation of the Arabic language curriculum during the reform era, from KBK and KTSP to the 2013 Curriculum, has affected students' Arabic language proficiency. The findings indicate that the Arabic language curriculum's execution aligns with academic conventions and supports student learning. The study reveals that the implementation of the Arabic language curriculum runs smoothly in Madrasah Aliyah Negeri 1 Metro City. The teacher regularly evaluates students through questions on the categorization of Arabic words - isim, fi'il, and letters- and their associated divisions and characteristics. As part of this process, students must memorize and comprehend 200-300 vocabularies and engage in spoken communication in Arabic. The teacher serves as a facilitator and guide to aid students in learning the language. The new curriculum's implications for teaching and learning activities are relevant, although objective evaluations are required. Students can learn independently and think critically, enhancing their linguistic abilities. The field provides substantial opportunities for students to broaden their knowledge and understanding of the Arabic language.